Appendicitis risk prediction models in children presenting with right iliac fossa pain (RIFT study): a prospective, multicentre validation study - RIFT Study Group on behalf of the West Midlands Research Collaborative; Fawkner-Corbett, DW (Elsevier, 2020)
BACKGROUND: Acute appendicitis is the most common surgical emergency in children. Differentiation of acute appendicitis from conditions that do not require operative management can be challenging in children. This study aimed to identify the optimum risk prediction model to stratify acute appendicitis risk in children.